Glacier Volume Estimation Using the Glaptop Model in the Cordillera Blanca of Peru - Quispe, M Zapana; Murillo, R Peña; Huerta, Y Pachac (ESPOCH Congresses: The Ecuadorian Journal of S.T.E.A.M., 2024)
The spatial retreat of glaciers located in the Peruvian Andes is closely linked to global climate change. The glaciers of the Checquiaraju micro-basin of the Cordillera Blanca are the main sources of water for the Andean zone; however, they have been suffering an accelerated space retreat. Remote sensing and geographic information systems (GIS) techniques have been applied to estimate the variation in glacier area and volume from LANDSAT 5 images. Glacier area and volume results are correlated with normalized difference snow index (NDSI) data to discriminate the snow cover from the rest of the elements in the image through the digital numbers (DN) of two bands: the TM blue band and shortwave infrared. The glacial zone was separated from the non-glacial zone for a better fit with the glacier limits seen in the composite color image. Subsequently, the delimitation of the glacier cover was refined through supervised classification, and finally, the determination of the volume of the glacier was estimated using the Glabtop model. The evolution of the glacier area of the Checquiaraju micro-basin tends to retreat. In the period 1989–2004, the glacier area of the study area decreased by 0.44 km2 (representing 11.3% of the glacier area in 1989), considering a rate of decrease of 0.0275 km2/year, which shows the retreat of glaciers in the area, which is a source of supply. Keywords: Checquiaraju, SIG, LANDSAT 5, NDSI, Glabtop. Resumen El retroceso espacial de los glaciares ubicados en los Andes peruanos está estrechamente vinculado al cambio climático global. Los glaciares de la microcuenca de Checquiaraju de la Cordillera Blanca son una fuente de agua muy importante para la zona andina; pero ellos vienen sufriendo un retroceso espacial acelerado. Se ha aplicado las técnicas de la Teledetección y Sistemas de Información Geográfica (SIG) para estimar la variación del área y volumen glaciar a partir de imágenes LANDSAT 5. Los resultados de área y volumen glaciar se correlacionan con datos de NDSI (Normalized Difference Snow Index) para discriminar la cobertura nival del resto de los elementos en la imagen, a través de los números digitales (DN) de dos bandas TM banda en azul e infrarroja de onda corta. Se separó la zona glaciar de la zona no – glaciar para un mejor ajuste con los límites de glaciar visto en la imagen de color compuesta. Posterior se refinó la delimitación de la cobertura glaciar a través de la clasificación supervisada y finalmente la determinación del volumen del glaciar se estimó mediante el modelo Glabtop. La evolución del área glaciar de la microcuenca de Checquiaraju tiene una tendencia al retroceso. En el periodo 1989 – 2004, el área glaciar de la zona de estudio se redujo 0,44 km2 (lo que representa el 11,3 % del área glaciar en 1989), considerando una tasa de disminución de 0,0275 km2/año, lo que evidencia el retroceso de los glaciares en la zona, la cual es fuente de abastecimiento. Palabras Clave: Checquiaraju, SIG, LANDSAT 5, NDSI, Glabtop.